Female protagonism in ancient Christianity: The experiences of Perpetua of Carthage (203 AD) - Pavani, Roney Marcos (Romanitas - Revista de Estudos Grecolatinos, 2023)
Our article proposes, from the Acts of Perpetua and Felicity (203 AD) – an account of a woman newly converted to Christianity – to analyze how Christian women in Roman society, and in third-century Carthage in particular, were no exactly invisible, but made invisible. That was done through a constant work of discipline and framing, which came from both intellectuals and civil and religious authorities. However, obscuring women’s stories involving martyrdom and their effective action within communities did not always work. This is attested by Perpetua’s account, as well as a multitude of other so-called apocryphal Christian texts. These texts represent a milestone of the early Christianity, which, in many of its aspects, and to a greater or lesser extent, made women come out of their penumbra to assume new identities.
Keywords: History of Women; History of Christianity; Early Roman Empire; Carthage; Perpetua